Influência de diferentes concentrações de flúor na água em indicadores epidemiológicos de saúde/doença bucal - Carvalho, Raquel Baroni de; Medeiros, Urubatan Vieira de; Santos, Karina Tonini dos [UNESP]; Pacheco Filho, Antônio Carlos [UNESP] (Associação Brasileira de Saúde Coletiva (ABRASCO), 2011)
O objetivo deste estudo foi avaliar o acesso a fontes de fluoreto e as condições de saúde bucal de 237 escolares de nove a dezesseis anos, de três localidades com diferentes concentrações de fluoreto na água. O teor de flúor na água de cada região foi analisado pela técnica do eletrodo seletivo para o íon flúor e a foi avaliada prevalência de cárie e fluorose, respectivamente, pelo índice CPOD e TSIF, apresentando diferença estatisticamente significante (ANOVA; p < 0,05) nas três localidades: área sem fluoretação artificial (CPOD 5,32 ± 3,49) e 16% de fluorose; área com fluoretação artificial de 0,8 ppmF (CPOD 1,88 ± 2,22) e 94% de fluorose; área com fluoretação natural de 2,54 ppmF (CPOD 3,96 ± 2,38) e 100% de fluorose. Os achados sugerem que os indicadores epidemiológicos de saúde/doença bucal estudados são influenciados pela presença de fluoreto na água de consumo e que a supervisão e a orientação são fundamentais na correta utilização dos compostos fluoretados, aproveitando-se o máximo benefício no controle da cárie dentária com o mínimo risco de ocorrência de fluorose.

The scope of this study was to evaluate access to fluoride sources and oral health hygiene of 237 schoolchildren aged nine to sixteen, from three locations with different fluoride concentrations in the water. The fluoride level in the water of each area was analyzed by the selective electrode technique for the fluoride ion and the prevalence of dental caries and fluorosis were evaluated, respectively, by the DMFT and TSIF index, revealing a statistically significant difference (ANOVA; p <0,05) in the three locations: area without artificial fluoridation (DMTF 5.32 ± 3.49) and 16% of dental fluorosis; area with artificial fluoridation of 0.8 ppmF (DMTF 1.88 ± 2.22) and 94% of dental fluorosis; area with natural fluoridation of 2.54 ppmF (DMTF 3.96 ± 2.38) and 100% of dental fluorosis. The findings suggest that the epidemiologic indicators of oral health/disease are influenced by the presence of fluoride in the water supply and that supervision and orientation are fundamental in the correct use of fluoridated compositions, taking advantage of the maximum benefit in the control of dental caries with minimum risk of the occurrence of dental fluorosis.
Influence of different concentrations of fluoride in the water on epidemiologic indicators of oral health/disease
Keywords: Epidemiologia; Saúde bucal; Saúde pública; Epidemiology; Oral health; Public health